استخدام التحليل العاملي لتحديد اهم المشاكل المؤثرة في جودة الامتحانات في جامعة الحمدانية - فداء نوئيل عبد الاحد; نوفل علي زكر; هاني صبري اليونس (PROSPECTIVE RESEARCHES, 2023)
The factor analysis is one of significant statistical methods that aims to study various phenomena, to extract the most important factors that affected it by analyzing the correlation coefficient between the variables of the studied phenomenon. It also distinguishes by the ability to shorten many variables and arrange them in a small number of factors in the form of linear compounds. In this research we studied the most important variables affecting the process and quality of the examinations based on a set of measurements for each of the variables taken in the study, which was applied at Al-Hamdaniya University which considered one of the new universities that has faced difficult conditions Due to its location in a geographical area that has been exposed to many crises. The study found that the examination questions in all their details were the basis that had the greatest impact on the exams, in additional of examination committee’s business and the other variables disproportionately.